2003
DOI: 10.1016/s0042-6822(03)00431-8
|View full text |Cite
|
Sign up to set email alerts
|

DNA synthesis-dependent relief of repression of transcription from the adenovirus type 2 IVa2 promoter by a cellular protein

Abstract: The promoter of the human adenovirus type 2 IVa(2) gene, which becomes active only during the late phase of infection, is built largely from sequences spanning, and downstream of, the sites of initiation of transcription. These sequences comprise an initiator, an intragenic sequence necessary for efficient transcription from the promoter by RNA polymerase II, and an intragenic binding site for a cellular repressor of IVa(2) transcription. The properties of the latter protein, which is termed IVa(2)-RF, suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…Regulation of mRNA export during adenovirus infection and the roles of the E1B 55-kDa and E4 Orf 6 proteins in this process were first identified for HeLa (6,19,73,96), a tumor-derived cell line. More importantly, in these tumor cells at 37°C, the reductions in viral late mRNA export efficiency observed in the absence of the E1B 55-kDa protein (39,52,73,96) are similar to or greater in magnitude than that measured in ONYX015-infected small airway epithelial cells (68). Rather, the data available from these and many previous studies of the basis of selective replication of E1B 55-kDa-null mutants (21,68) suggest that multiple functions of the E1B 55-kDa protein can be important for Ad5 replication.…”
Section: Discussionmentioning
confidence: 93%
“…Regulation of mRNA export during adenovirus infection and the roles of the E1B 55-kDa and E4 Orf 6 proteins in this process were first identified for HeLa (6,19,73,96), a tumor-derived cell line. More importantly, in these tumor cells at 37°C, the reductions in viral late mRNA export efficiency observed in the absence of the E1B 55-kDa protein (39,52,73,96) are similar to or greater in magnitude than that measured in ONYX015-infected small airway epithelial cells (68). Rather, the data available from these and many previous studies of the basis of selective replication of E1B 55-kDa-null mutants (21,68) suggest that multiple functions of the E1B 55-kDa protein can be important for Ad5 replication.…”
Section: Discussionmentioning
confidence: 93%
“…Whereas early-phase gene products are primarily concerned with providing the ideal environment for viral DNA replication, the late genes encode predominantly the structural proteins that allow the assembly of the virus particle (1). Gene expression switches from early to late via a small class of intermediate genes that become activated around the time that viral DNA replication begins (24). These events have been most widely studied in human adenovirus type 5 (HAdV-C5 [Ad5]).…”
Section: Introductionmentioning
confidence: 99%
“…MLP activation is achieved upon the onset of viral DNA replication by the intermediate gene products IX and IVa2, the latter in conjunction with the L4 products 22K and/or 33K (79). IVa2 expression commences after an unknown cellular repressor bound to its promoter is titrated out by the excess of nascent viral genomes (2, 3). Upon activation of the MLP, L4-22K and L4-33K additionally contribute to the correct expression of the full repertoire of adenovirus late proteins by influencing the splicing of the MLTU pre-mRNA (1012); L4-22K also cooperates with IVa2 to promote packaging of viral DNA into nascent capsids (7).…”
Section: Introductionmentioning
confidence: 99%
“…Expression of pIX, IVa2, and late genes of Ad is detected only after Ad DNA synthesis has occurred. It has been shown that IVa2 transcription is regulated by a cellular repressor that is titrated out upon Ad genome replication (17,18), and MLP is regulated by IVa2 in conjunction with the late L4-22K and -33K proteins (2,26). Our previous study had shown that UXP expression is detected only in cells at the late stage of infection; no UXP was detected in the presence of cytosine arabinoside (an inhibitor of DNA replication).…”
Section: Discussionmentioning
confidence: 99%
“…The same phenomenon was demonstrated for the Ad IVa2 promoter. The IVa2 promoter was unable to drive efficient synthesis of GFP in the absence of a simian virus 40 (SV40) origin of replication in a reporter assay in a transient-transfection system (17). Furthermore, it has been well documented in superinfection experiments that replication of the DNA template is required for maximal activation of expression of pIX, IVa2, and late-region L2 to L5 proteins (11,24,37).…”
Section: Discussionmentioning
confidence: 99%